Associations among the home language environment and neural activity during infancy. (June 2020) - Brito, Natalie H.; Troller-Renfree, Sonya V.; Leon-Santos, Ana; Isler, Joseph R.; Fifer, William P.; Noble, Kimberly G.
Abstract: Characteristics of the home language environment, independent of socioeconomic background, may account for disparities in early language abilities. Past studies have reported links between the quantity of language input within the home and differences in brain function during early childhood. The current study examined associations between home language input and EEG brain activity in a socioeconomically diverse sample of 6- to 12-month-old infants (N = 94). Replicating past studies, a positive correlation was found between measures of socioeconomic status and language input. Examining links between language input and brain activity, analyses yielded a negative association, with children who heard more adult words in the home demonstrating reduced EEG beta power (13–19 Hz) in the parietal region. Exploratory analyses revealed a significant interaction between language input and the amount of chaos and disorganization in the home. Specifically, among children living in high-chaos households, children who heard more adult words tended to have reduced EEG activity. Among children living in low-chaos homes, there was no link between adult word count and children's EEG activity. These findings demonstrate the importance of the early home environment context in shaping neurocognitive trajectories.